Wpływ użytej w wypowiedzi leksyki potocznej na wizerunek felietonisty - Barańska-Szmitko, Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article presents the research results about the influence of the colloquial lexis used in a column’s language on the image of the author of the text, as well as describing the mechanism of this influence. The material was collected during empirical research, when respondents pointed to traits of the column’s author after reading his/her text, and subsequently wrote the text fragments which in their opinion represented the indicated attributes. The exploratory discourse analysis of this corpus made it possible to identify words or sentences indicating the communication of traits like “humorous”, “ironic”, “interesting writer” through the use of colloquial lexis. This article is the analysis of the communicative mechanism of constructing these attributes.